A method for improving the electrochemical performance of graphite negative electrode

By using a chemically diazotated chemical covalent grafting phenol layer on the surface of graphite particles to form a Gr-Ph-x composite, the problem that graphite negative electrode depends on electrolyte in lithium batteries is solved, and a significant improvement in specific capacity, rate performance and cycle stability is achieved.

CN115172682BActive Publication Date: 2025-03-11DONGGUAN MICRO CRYSTAL QIANYAN TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210685799.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-16
Publication Date
2025-03-11
Estimated Expiration
2042-06-16

AI Technical Summary

Technical Problem

The electrochemical performance of graphite negative electrodes in lithium batteries depends on the electrolyte, which easily leads to peeling, resulting in capacity attenuation and reduced service life. It is difficult for the prior art to improve its specific capacity, rate performance and cycle stability at the same time.

Method used

The phenol layer is covalently grafted on the surface of graphite particles by diazotization chemistry to form the graphite/phenol layer composite Gr-Ph-x, the mole percentage of 4-amine phenol and graphite is regulated, and the thickness of the phenol layer and the roughness of the graphite surface are controlled.

Benefits of technology

The specific capacity, rate performance and cycle stability of the graphite negative electrode are improved, and a stable solid electrolyte interface is formed, which inhibits the direct contact between graphite and electrolyte, and extends the life of the lithium battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115172682B_ABST
    Figure CN115172682B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for improving the electrochemical performance of graphite negative electrode, and belongs to the field of electrochemical energy storage technology. A phenol layer is covalently grafted on the surface of graphite particles by diazo chemistry, and the grafted phenol layer can not only prevent the graphite from directly contacting the electrolyte, inhibit the graphite from peeling off, and improve the electrochemical cycle stability of the graphite; but also can electrochemically store energy and improve electrode kinetics, and improve the specific capacity and rate performance of the graphite.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemical energy storage and relates to a method for diazotizing a grafted phenol layer on a graphite surface to improve the electrochemical performance thereof. Background Art

[0002] Graphite has the advantages of high electrical conductivity, good rate performance, small volume expansion rate after lithium insertion, and low cost. Since the commercialization of lithium-ion batteries (hereinafter referred to as lithium batteries) in 1991, graphite has always dominated the negative electrode of lithium batteries (Chemical Society Reviews, 49 (2020) 3806-383; Angewandte Chemie International Edition, 59 (2019) 110-135). However, the electrochemical performance of graphite negative electrodes is highly dependent on the electrolyte of lithium batteries. For example, using ether, sulfone, and sulfoxide compounds as solvents can easily lead to graphite exfoliation, resulting in lithium battery capacity decay and reduced life (ACS Energy Letters, 3 (2018) 335-340); even when running in a second-generation electrolyte with ethylene carbonate-ethyl methyl carbonate (EC-EMC) as a solvent, when the rate exceeds 1C, graphite is easily exfoliated, causing the lithium battery capacity to decay rapidly (Electrochemistry Communications, 97 (2018) 37-41).

[0003] In order to improve the electrochemical stability of graphite anode, researchers have developed a variety of methods. For example, the use of new binders (Journal of Power Sources, 247 (2014) 981-990), reducing Li +The interaction strength with the solvent (ACS Energy Letters, 3 (2018) 335-340), the use of high-concentration electrolyte (Nano Letters, 17 (2017) 1602-1609), the addition of additives to carbonate solvents (Journal of The Electrochemical Society, 162 (2015) A7008-A7014; Journal of Power Sources, 251 (2014) 311-318), and surface modification (Advanced Materials, 27 (2015) 130-137; Nature Energy, 1 (2016) 16113; Journal of Materials Chemistry, 17 (2007) 329-334), etc. All of these methods allow a stable solid electrolyte interface (SEI) or protective layer to form on the graphite surface. The formation of SEI is beneficial to the isolation of graphite from the electrolyte, preventing the continuous decomposition of the electrolyte and inhibiting the interaction of solvent molecules with Li + The co-deintercalation of graphite minimizes graphite exfoliation (Chemical Reviews, 104 (2004) 4303-4418). Obviously, surface modification is the most direct and simple method to construct an artificial protective layer on the graphite surface.

[0004] CN201410340471.7 discloses a multi-component composite negative electrode material and a preparation method thereof, as well as a lithium-ion battery using the negative electrode material. The multi-component composite negative electrode material for lithium-ion batteries is a multi-shell core-shell structure, wherein the core is graphite and a nano-active substance coated on the graphite surface, the first shell is a conductive carbon material, the second shell is a nano-active substance, and the third shell is a conductive carbon material coating layer. The invention adopts a coating treatment technology to coat the graphite surface with a nano-active substance to obtain a first precursor; then the first precursor is subjected to surface composite modification using a conductive carbon material to obtain a second precursor; next, the nano-active substance is coated on the surface of the second precursor to obtain a third precursor; finally, the third precursor is coated and modified to obtain a multi-component composite electrode material. However, the preparation of the multi-component composite negative electrode material involves high-temperature heat treatment, crushing, screening, demagnetization and other processes, and the steps are cumbersome.

[0005] The structure of the graphite surface modification layer and the stability of the SEI formed subsequently determine the electrochemical performance of the graphite negative electrode. A generally accepted view is that covalently grafting a protective layer on the graphite surface is conducive to the stability of the subsequent SEI (Journal of Materials Chemistry, 17 (2007) 329-334); however, due to the chemical inertness of graphite, it is not easy to covalently graft a protective layer on the graphite surface.

[0006] According to the literature, there are two main methods for forming covalent bonds at the graphite / protective layer interface, one is the fluorination method (Journal of Fluorine Chemistry, 126 (2005) 1111-1116), and the other is the diazotization method (Chemistry of Materials, 17 (2005) 1717-1721; Carbon, 92 (2015) 362-381). The fluorination method mainly uses gas F2, which is highly toxic and environmentally unfriendly; while diazotization can graft a variety of functionalized protective layers on the graphite surface. Although there are literature reports that the use of diazo chemistry to covalently graft a nitro-containing protective layer on the graphite surface can improve the electrochemical properties of graphite, the literature only conducted 0.2mV s on modified and unmodified graphite samples. –1 The electrochemical performance of the graphite was compared with that of the graphite with 30 cycles, and there is no record in the literature that the nitro-modified layer can improve the specific capacity and rate performance of graphite (Journal of Materials Chemistry, 17 (2007) 329-334). Therefore, whether the use of diazo chemistry can obtain modified graphite with improved specific capacity, rate performance and cycle stability is still an unknown research field. Summary of the invention

[0007] In view of the deficiencies in the prior art, the present invention provides a method for improving the electrochemical performance of a graphite negative electrode, which can simultaneously improve the specific capacity, rate performance and cycle stability of the graphite negative electrode.

[0008] A method for improving the electrochemical performance of a graphite negative electrode, characterized in that a phenol layer is covalently grafted onto the surface of graphite particles using diazo chemistry to form a graphite / phenol layer composite, abbreviated as Gr-Ph-x, wherein Gr represents graphite, Ph represents the phenol layer, and x is the molar percentage of 4-aminophenol to graphite.

[0009] The XRD spectrum of the Gr-Ph-x showed a new diffraction peak at 17.9°; the (001) crystal plane shifted to the low-angle region. Using TEM technology, the interplanar spacing of the (002) crystal plane of Gr-Ph-5 was 0.347nm. The thickness of the phenol layer was 2–6nm.

[0010] In the FT-IR image, OH stretching vibration (3430 cm -1 ), CO stretching vibration (1116cm -1 ) and benzene ring breathing vibration peak (1506-1634cm -1 ) peak enhancement.

[0011] In the C 1s spectrum ( Fig.16), the fitting peaks at 284.8, 285.1 and 286.2 eV correspond to C=C, CC(N,O) and C=O components respectively. Fig.17 ), the fitting peaks at 399.6 and 400.2 eV correspond to NC and N=N components, respectively. Fig.18 ), the fitting peaks at 530.5, 532.0 and 533.4 eV correspond to C=O, C-OH (C) and surface adsorbed oxygen (O a ).

[0012] The preparation process of the Gr-Ph-x comprises the following steps:

[0013] a. Transfer an appropriate amount of graphite and fresh 4-aminophenol (hereinafter referred to as 4-aminophenol) into anhydrous acetonitrile solution and stir for 0.5-1h under nitrogen protection to obtain a mixed solution A;

[0014] b. Add an appropriate amount of tert-butyl nitrite to the mixed solution A, and stir at room temperature under nitrogen protection for 12-48 hours to obtain a mixed solution B;

[0015] c. The mixed solution B is subjected to solid-liquid separation, the liquid is recovered, and the solid is dried under vacuum conditions to obtain Gr-Ph-x.

[0016] In step a, the appropriate amount of graphite and fresh 4-aminophenol are used, wherein the molar percentage of 4-aminophenol to graphite is 3-10. The fresh 4-aminophenol refers to colorless crystals of unoxidized 4-aminophenol.

[0017] The anhydrous acetonitrile described in step a is The analytically pure acetonitrile obtained after molecular sieve drying treatment includes: The mass / volume of molecular sieve and acetonitrile is 0.2 g mL –1 , the drying time is 5-7 days, and the drying temperature is room temperature.

[0018] The anhydrous acetonitrile solution in step a, wherein the mass / volume ratio of graphite to anhydrous acetonitrile is 0.006-0.012 g mL –1 .

[0019] The nitrogen protection in steps a and b, wherein the nitrogen flow rate is 5-20 mL min –1 .

[0020] The appropriate amount of tert-butyl nitrite in step b, wherein the molar ratio of tert-butyl nitrite to 4-aminophenol is (3-10):1.

[0021] The solid-liquid separation in step c is carried out by centrifugal separation or vacuum filtration separation.

[0022] As described in step c, drying is performed under vacuum conditions, wherein the vacuum degree is 0.09-0.1 MPa, the drying temperature is 60-80° C., and the drying time is 6-12 h.

[0023] The present invention also provides the use of Gr-Ph-x for assembling Li||Gr-Ph-x lithium battery.

[0024] Beneficial Effects

[0025] 1. The method for improving the electrochemical performance of graphite negative electrode provided by the present invention has mild reaction conditions, simple process and is easy for large-scale industrial production.

[0026] 2. The method for improving the electrochemical performance of graphite negative electrode provided by the present invention can not only improve the electrochemical cycle stability of graphite, but also simultaneously improve the specific capacity and rate performance of graphite. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 XRD patterns of the samples.

[0028] Figure 2 A local magnified image of the sample's XRD pattern.

[0029] Figure 3 Mechanism of diazotization grafted phenol layer on graphite surface: (a) formation of 4-hydroxybenzene cation and 4-hydroxydiazonium benzene cation; (b) grafted phenol layer; (c) formation of Gr-Ph-x.

[0030] Figure 4 This is the SEM image of the initial graphite (low magnification).

[0031] Figure 5 This is the SEM image of the initial graphite (high magnification).

[0032] Figure 6 This is the SEM image of Gr-Ph-3 (low magnification).

[0033] Figure 7 This is the SEM image of Gr-Ph-3 (high magnification).

[0034] Figure 8 This is the SEM image of Gr-Ph-5 (low magnification).

[0035] Fig. 9 This is the SEM image of Gr-Ph-5 (high magnification).

[0036] Fig.10 This is the SEM image of Gr-Ph-10 (low magnification).

[0037] Fig.11 This is the SEM image of Gr-Ph-10 (high magnification).

[0038] Fig.12 This is the TEM image of Gr-Ph-5.

[0039] Fig.13 For the corresponding Fig.12 High-resolution TEM image of the circled area.

[0040] Fig.14 The atomic percentage of C in Gr-Ph-5 changes with Ar + Variation curve of sputtering depth.

[0041] Fig.15 This is the FT-IR graph of the sample.

[0042] Fig.16 is the C1s spectrum of the sample.

[0043] Fig.17 N1s spectrum of the sample.

[0044] Fig.18 This is the O1s spectrum of the sample.

[0045] Fig.19 Cyclic voltammograms of different graphite anodes.

[0046] Fig. 20 Nyquist plots of different graphite anodes.

[0047] Fig.21 Charge and discharge curves of different graphite anodes at 0.1C.

[0048] Fig. 22 Rate performance diagram of different graphite anodes.

[0049] Fig.23 Cycling curves of different graphite anodes. DETAILED DESCRIPTION

[0050] The technical solution of the present invention is further described below through specific embodiments in combination with the accompanying drawings. These embodiments are only for illustrating the technical solution of the present invention and cannot be regarded as limiting the content of the claims of the present invention.

[0051] 4-Aminophenol, acetonitrile, tert-butyl nitrite, and N-methylpyrrolidone in the examples were purchased from Shanghai Sinopharm Chemical Reagent Co., Ltd., copper foil, acetylene black, polyvinylidene fluoride, and Celgard 2400 microporous polypropylene membrane were purchased from Taobao Jinghong New Energy, and graphite was purchased from Shenzhen Bettery New Energy Materials Co., Ltd.

[0052] The X-ray powder diffraction spectrum (XRD) was obtained by using a German Bruker D8Advance powder diffractometer; the scanning electron microscope (SEM) was obtained by using a Japanese Hitachi Regulus8220 field emission scanning electron microscope; the transmission electron microscope (TEM) was obtained by using a Japanese JEOL JEM-2100 transmission electron microscope; the Auger electron spectrum (AES) was obtained by using a US ThermoFisher ESCALAB 250Xi-AER Auger electron spectrometer; the infrared spectrum (FT-IR) was obtained by using a US Nicolet10 infrared spectrometer; the X-ray photoelectron spectroscopy (XPS) was obtained by using a US Fisher Scientific ESCALAB Xi + The electrochemical properties of the sample electrodes were obtained by X-ray photoelectron spectrometer detection; the electrochemical properties of the sample electrodes were obtained by Shanghai Chenhua CHI760E electrochemical analyzer and Wuhan Landian LANHE CT2001A battery testing system.

[0053] Example 1

[0054] The preparation steps of Gr-Ph-3 are as follows:

[0055] a. Transfer 0.3 g (25 mmol) of graphite and 0.082 g (0.75 mmol) of 4-aminophenol to 25 mL of anhydrous acetonitrile solution and stir under nitrogen for 0.5 h to obtain a mixed solution A;

[0056] b. Add 0.9 mL (7.5 mmol) of tert-butyl nitrite to the mixed solution A and stir at room temperature under nitrogen for 12 h to obtain a mixed solution B;

[0057] c. The mixed solution B was centrifuged to recover the liquid and the solid was dried in a vacuum drying oven at 60°C (vacuum degree of 0.09-0.1MPa) for 12h to obtain Gr-Ph-3.

[0058] Example 2

[0059] The preparation steps of Gr-Ph-5 are as follows:

[0060] a. Transfer 0.3 g (25 mmol) of graphite and 0.136 g (1.25 mmol) of 4-aminophenol to 50 mL of anhydrous acetonitrile solution and stir under nitrogen for 1 h to obtain a mixed solution A;

[0061] b. Add 0.9 mL (7.5 mmol) of tert-butyl nitrite to the mixed solution A and stir at room temperature under nitrogen for 24 h to obtain a mixed solution B;

[0062] c. The mixed solution B was separated by filtration, the liquid was recovered, and the solid was dried in a vacuum drying oven at 70°C (vacuum degree of 0.09-0.1MPa) for 10 hours to obtain Gr-Ph-5.

[0063] Example 3

[0064] The preparation steps of Gr-Ph-10 are as follows:

[0065] a. Transfer 0.3 g (25 mmol) of graphite and 0.272 g (2.5 mmol) of 4-aminophenol to 50 mL of anhydrous acetonitrile solution and stir under nitrogen for 1 h to obtain a mixed solution A;

[0066] b. Add 0.9 mL (7.5 mmol) of tert-butyl nitrite to the mixed solution A and stir at room temperature under nitrogen for 48 h to obtain a mixed solution B;

[0067] c. The mixed solution B was separated by filtration, the liquid was recovered, and the solid was dried in a vacuum drying oven at 80°C (vacuum degree of 0.09-0.1MPa) for 6 hours to obtain Gr-Ph-10.

[0068] Results Analysis

[0069] Figure 1 is the XRD pattern of graphite sample. Figure 1 It can be seen that 7 diffraction peaks appeared in the initial graphite, corresponding to the (002), (100), (101), (004), (103), (110) and (112) crystal planes of hexagonal graphite (PDF#41-1487) with space group P63 / mmc(194). The XRD spectrum of the surface diazotized graphite sample is different from that of the initial graphite in that: (1) a new diffraction peak appears at 17.9°; (2) the intensity of each diffraction peak is reduced; (3) the (00l) crystal plane shifts to the low angle region ( Figure 2 ). The new peak at 17.9° is attributed to the phenol layer after diazotization. The decrease in the intensity of each diffraction peak after diazotization is attributed to the coating of graphite by the phenol layer. The movement of the (00l) crystal plane in the low-angle region is attributed to the expansion of the interlayer spacing of the graphite (00l) crystal plane. This shows that the covalent grafting effect of phenol on the graphite surface defect site ( Figure 3 ) can expand the distance between graphite layers, which is beneficial to improving the rate performance of Gr-Ph-x because the lithium ions tend to be inserted and removed from the graphite layers in a direction parallel to the (00l) crystal plane (ASC Nano, 7 (2013) 2773–2780).

[0070] Before the diazotization reaction, the surface of graphite particles is relatively smooth ( Figure 4 ), but there are slight cracks ( Figure 5After diazotization, as x increases to 3, the surface roughness of graphite particles decreases significantly ( Figure 6 ), no cracks were observed Figure 7 As x increases to 5, the surface of graphite particles becomes smooth and dense ( Figure 8 and Fig. 9 ). As x continues to increase to 10, the surface of the graphite particles becomes rough and porous ( Fig.10 and Fig.11 )). SEM results show that the surface structure of graphite can be regulated by changing the molar percentage of 4-aminophenol to graphite. A smooth and dense surface is conducive to the subsequent formation of a stable SEI (solid electrolyte interface).

[0071] Using TEM technology ( Fig.12 ), the modified layer on the surface of graphite particles can be observed, and the interplanar spacing of graphite can be measured. Taking Gr-Ph-5 as an example, the interplanar spacing of its (002) crystal plane is measured to be 0.347nm, which is larger than the 0.335nm of the initial graphite ( Fig.13 ), which shows that after diazotization, the spacing between graphite (00l) planes is indeed enlarged, which is consistent with the XRD results. Fig.13 It can be judged that the thickness of the phenol layer is 2–6 nm.

[0072] The thickness of the phenol layer can be further estimated using AES depth analysis. Fig.14 The effects of the atomic percentage of carbon in Gr-Ph-5 on Ar + The variation curve of sputtering depth. Fig.14 It can be seen that with the increase of sputtering depth, the content of carbon element gradually increases and stabilizes at a sputtering depth of about 6nm. This shows that the thickness of the phenol layer is about 6nm, which is consistent with Fig.13 The results are consistent.

[0073] The phenol layer on the graphite surface can be analyzed using FT-IR technology. Fig.15 This is the FT-IR image of the sample. Located at 3300, 1381, 1116–1004 cm –1 The peaks at 3430cm and 3470cm are respectively attributed to O–H stretching vibration, O–H in-plane bending vibration and C–O / C–OH stretching vibration (Acta Chimica Slovenica, 52 (2005) 238–244; Journal of Heterocyclic Chemistry, 54 (2017) 758-763); this indicates that the initial graphite surface contains hydroxyl functional groups. After surface diazotization, the intensity of the characteristic peaks related to phenol is significantly enhanced, such as OH stretching vibration (3430cm -1 ), CO stretching vibration (1116cm -1) and benzene ring breathing vibration peak (1506-1634cm -1 )(Journal of Heterocyclic Chemistry, 54(2017)758-763).

[0074] Furthermore, the formation of the phenol layer on the graphite surface was supported by the results of the high-resolution XPS spectra of C1s, N 1s and O1s. Fig.16 ), the fitting peaks at 284.8, 285.1 and 286.2 eV correspond to C=C, CC(N,O) and C=O components respectively (Environmental Science&Technology, 50(2016)10978-10987). Fig.17 ), the fitting peaks at 399.6 and 400.2 eV correspond to NC and N=N components respectively (Langmuir, 23 (2007) 11074-11082). Fig.18 ), the fitting peaks at 530.5, 532.0 and 533.4 eV correspond to C=O, C-OH (C) and surface adsorbed oxygen (O a )(Journal of Materials Chemistry A, 3(2015) 21257-21268). It should be noted that with the increase of x value in Gr-Ph-x, the N 1s and O1s peak intensities gradually increase, which is attributed to the increase in the thickness of the phenol layer containing azo bonds and phenolic hydroxyl groups ( Figure 3 ). In addition, with the increase of x value, the content of C=C component in C 1s decreases, while the content of CN component and CO component in O1s increases (Table 1); these results all indicate that the thickness of the phenol layer increases with the increase of x value.

[0075] Table 1 Peak positions and contents of components in C 1s, N 1s, and O 1s

[0076]

[0077] Based on the above analysis of the results, the present invention uses diazo chemistry to grow a phenol layer on the surface of graphite particles, and controls the molar percentage of 4-aminophenol / graphite, so as to achieve the regulation of the thickness of the phenol layer and the surface roughness of the graphite particles; this lays a foundation for studying the influence of diazo grafted phenol on the graphite surface on its electrochemical properties.

[0078] Example 4

[0079] Assembly of Li∥Gr-Ph-3 lithium battery:

[0080] 1) Take an appropriate amount of Gr-Ph-3 (or Gr-Ph-5, Gr-Ph-10), acetylene black and polyvinylidene fluoride (mass ratio 8:1:1), transfer them to an agate mortar, add an appropriate amount of N-methylpyrrolidone, grind them thoroughly, and prepare a slurry;

[0081] 2) The slurry is evenly coated on a copper foil (current collector), and then placed in a vacuum drying oven and dried at 80° C. for 12 h to obtain a Gr-Ph-3 (or Gr-Ph-5, Gr-Ph-10) working electrode.

[0082] 3) Use commercially available 1 mol L –1 A mixture of ethylene carbonate-dimethyl carbonate-diethyl carbonate (volume ratio of 1:1:1) of LiPF6 was used as the electrolyte, Celgard 2400 microporous polypropylene membrane was used as the diaphragm, a lithium sheet was used as the counter electrode, and a Gr-Ph-3 (or Gr-Ph-5, Gr-Ph-10) working electrode was used as the working electrode to assemble an R2032 type lithium button battery.

[0083] Results Analysis

[0084] Fig.19 The cyclic voltammetry (CV) diagrams of different graphite anodes are given. The reduction peak starting at 1.1V and centered at about 0.71V in the first cycle of the CV curve is attributed to the decomposition of the electrolyte and the formation of SEI (Journal of The Electrochemical Society, 151 (2004) A1659; The Journal of Physical Chemistry C, 118 (2014) 6586-6593); the reduction peak at 0.15V and below is attributed to Li + embedded in the graphite interlayer; the oxidation peak at 0.26V is attributed to the delithiation of graphite (The Journal of Physical Chemistry C, 118 (2014) 6586-6593). The main difference between Li∥Gr-Ph-x and the initial graphite negative electrode is that Li + The distance between the insertion and extraction peaks is shortened, and the intensity of the solvent irreversible reduction peak at 0.71 V is weakened. This shows that the surface diazo grafted phenol layer improves the Li + The reversibility of the deintercalation reaction and the stability of the electrochemical reaction in the electrolyte (Electrochimica Acta, 47 (2002) 1423-1439).

[0085] The surface diazotization grafted phenol layer also improves the kinetics of the graphite electrode reaction. From the Nyquist plots of different graphite anodes ( Fig. 20 ) can be seen, representing the charge transfer impedance (R ct) decreased from 157.3Ω of the initial graphite to 105.9Ω of Gr-Ph-3, 63.7Ω of Gr-Ph-5, and 86.8Ω of Gr-Ph-10. ct The decrease of means the improvement of electrode reaction kinetics, that is, the improvement of electrode rate performance. This shows that the diazotized grafted phenol layer can improve the rate performance of graphite. In addition, with the increase of x value, R ct There is a phenomenon of first decreasing and then increasing, which is attributed to Li + The deintercalation rate is not linearly related to the increase of phenol layer thickness; it also shows that the appropriate phenol layer structure (roughness) and thickness are more conducive to Li + of disembedding.

[0086] It is worth mentioning that the diazotized grafted phenol layer can not only improve the rate performance of the graphite anode, but also improve its specific capacity and cycle stability. For example, at 0.1C (1C = 372 mA g -1 ), the discharge specific capacity and coulombic efficiency (CE) of Gr-Ph-x are improved ( Fig.21 ). At different current densities, Gr-Ph-x exhibits a higher specific capacity than the initial graphite ( Fig. 22 ); and after the current density gradually increased from 0.1C to 5C and then back to 0.1C, Gr-Ph-x showed higher specific capacity and capacity retention rate than the initial graphite.

[0087] Cycle 300 times at 1C ( Fig.23 ), the discharge specific capacities of Gr-Ph-3, Gr-Ph-5 and Gr-Ph-10 were maintained at 284, 361 and 314 mA h g -1 The capacity retention rates were 82.6%, 90.5% and 89.5%, respectively, which were much higher than the initial graphite retention capacity (156 mA h g -1 ) and capacity retention rate (54.2%).

[0088] In summary, the present invention uses diazo chemistry to covalently graft a phenol layer on the surface of graphite particles, providing a method with mild reaction conditions, controllable process, and easy scale-up for improving the electrochemical performance of graphite negative electrodes. The method for improving the electrochemical performance of graphite negative electrodes provided by the present invention can achieve the effect of "killing two birds with one stone", that is, not only preventing direct contact between graphite and electrolyte, inhibiting excessive decomposition of electrolyte and graphite stripping, and improving the electrochemical cycle stability of graphite by forming a phenol protective layer, but also the grafted phenol layer can improve electrode kinetics, realize electrochemical energy storage by utilizing the tautomerism of quinone / phenol structure during charge / discharge, and improve the rate performance and charge / discharge specific capacity of graphite.

Claims

1. A method for improving the electrochemical performance of a negative electrode of a graphite lithium battery, characterized in that: A phenol layer is covalently grafted onto the surface of graphite particles using diazo chemistry to form a graphite / phenol layer composite. The preparation method of the graphite / phenol layer composite comprises the following steps: a. Transfer graphite and 4-aminophenol into anhydrous acetonitrile solution and stir for 0.5–1 h under nitrogen protection to obtain mixed solution A; b. Add tert-butyl nitrite to the mixed solution A and stir at room temperature under nitrogen protection for 12–48 h to obtain a mixed solution B; c. The mixed solution B is subjected to solid-liquid separation, the liquid is recovered, and the solid is dried under vacuum conditions to obtain a graphite / phenol layer composite, referred to as Gr-Ph- x , where Gr represents graphite, Ph represents phenol layer, x is the molar percentage of 4-aminophenol to graphite, x= 3–10.

2. The method according to claim 1, characterized in that: The anhydrous acetonitrile in step a is analytically pure acetonitrile obtained after drying with a 4 Å molecular sieve, wherein the mass / volume of the 4 Å molecular sieve and acetonitrile is 0.2 g mL –1 , the drying time is 5–7 days, and the drying temperature is room temperature; The mass / volume ratio of graphite to anhydrous acetonitrile in step a is 0.006–0.012 g mL –1 .

3. The method according to claim 1, characterized in that: Nitrogen protection as described in steps a and b, with a nitrogen flow rate of 5–20 mL min –1 .

4. The method according to claim 1, characterized in that: In step b, the molar ratio of tert-butyl nitrite to 4-aminophenol is (3-10):

1.

5. The method according to claim 1, characterized in that: The solid-liquid separation in step c is carried out by centrifugal separation or vacuum filtration separation; In step c, the solid is dried under vacuum conditions with a vacuum degree of 0.09-0.1 MPa, a drying temperature of 60-80 °C, and a drying time of 6-12 h.

6. The method according to any one of claims 1 to 5, characterized in that: The thickness of the phenol layer was 2–6 nm.

7. The method according to any one of claims 1 to 5, characterized in that: The Gr-Ph- x , a new diffraction peak appeared at 17.9° in the XRD spectrum; the (001) crystal plane shifted to the low-angle region; using TEM technology to measure, the interplanar spacing of the (002) crystal plane of Gr-Ph-5 was 0.347 nm; In the FT-IR image, OH stretching vibration 3430 cm -1 、CO stretching vibration 1116 cm -1 and benzene ring breathing vibration peak 1506-1634 cm -1 Peak enhancement; In the C 1s spectrum, the fitting peaks at 284.8, 285.1 and 286.2 eV correspond to C=C, CC(N,O) and C=O components, respectively. In the N 1s spectrum, the fitting peaks at 399.6 and 400.2 eV correspond to NC and N=N components, respectively. In the O 1s spectrum, the fitting peaks at 530.5, 532.0 and 533.4 eV correspond to C=O, C-OH(C) and surface adsorbed oxygen, namely O a .

Citation Information

Patent Citations

  • Multi-component composite negative electrode material, preparation method of multi-component composite negative electrode material and lithium ion battery comprising multi-component composite negative electrode material

    CN104091934A